Arabic Conquests and Early Islamic Historiography: The Futuh al-Buldan of al-Baladhuri (by Ryan Lynch): I . B . Tauris, 2020. 272 pages. (American Journal of Islam and Society, 2022)
Ryan Lynch’s Arabic Conquests and Early Islamic Historiography: The Futuh al-Buldan of al-Baladhuri offers a new analysis of the famous history Kitāb Futūḥ al-buldān (The Book of the Conquest of Lands) by the 3rd/9th century Abbasid scholar Aḥmad b. Yaḥyā al- Balādhurī (d. ca. 279/892). Lynch handles the source well, supporting his own close reading of the text with a wealth of references to offer nuanced insight into the purpose, context, and content of this seminal source on early Islamic governance. His core thesis is that  Balādhurī composed his text as a handbook for the Abbasid court officials who had been struggling to balance the court budget,  collect provincial taxes,  and keep the imperial administrative system running in a politically-distraught time. Although Lynch’s argument is not entirely new,  his study, which is based on an admirably detailed analysis of Balādhurī’s work, will most likely serve as the standard reference book in the field.